STRATEGI KEMANDIRIAN MELALUI PROGRAM INOVASI DESA KUALA SEMPANG KABUPATEN BINTAN - Adji Suradji Muhammad; Putri Karuniyati; Mahadiansar Mahadiansar (Program Studi Ilmu Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam '45 (UNISMA) Bekasi, 2022)
One of the goals of the village innovation program is to improve the quality of the use of the Village Fund through various development activities that are part of the government's commitment to providing access to manage village potential and improve community welfare. Potential tourism objects, longan plantations, onions, and organic fertilizer management in Kuala Sempang Village, Srikuala Lobam Sub-district, Bintan Regency can be utilized through innovative villages because they have the potential to help the community's economic security. The purpose of this study is to know the Village Independence Strategy Through the Village Innovation Program. The research applies a qualitative approach. Data collection techniques through observation, in-depth interviews, and documentation. The results of study 1) Socio-cultural conditions still reflect the flexibility of the original culture in the village of Kuala Sempang and the program carried out received community support, 2) Economic resilience has increased from the previous year but still experienced obstacles such as limited manager skills, lack of community knowledge to participate in the program, 3) The environment and infrastructure are still experiencing obstacles. The village independence strategy through the innovation program in the village of Kuala Sempang has been quite optimal because it has referred to the achievement of program goals and objectives, even though it has not been running optimally. The recommendation of this research is that the government is expected to be able to encourage all villages to innovate so as to provide sustainable innovative ideas.